2017
DOI: 10.1073/pnas.1621349114
|View full text |Cite
|
Sign up to set email alerts
|

Metal-mediated diradical tuning for DNA replication arrest via template strand scission

Abstract: ) for Cu(PyED)·2Cl, indicating three nitrogens and a chloride in the psuedo-equatorial plane with the remaining pyridine nitrogen and solvent in axial positions. EPR spectra of the Cu(II) complexes exhibit an axially elongated octahedron. This spectroscopic evidence, together with density functional theory computed geometries, suggest six-coordinate structures for Cu(II) and Fe(II) complexes and a five-coordinate environment for Zn(II) analogs. Bergman cyclization via thermal activation of these constructs yie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 90 publications
1
24
0
Order By: Relevance
“…We sought to determine the mechanism by which hyperthermia potentiates metalloenediyne toxicity. In a recent study, Zaleski and co-workers (19) tested the ability of PyED or PyED-metalloenediyne complexes containing Cu(II), Fe (II), and Zn (II) to damage supercoiled DNA. They found that efficient nicking of the DNA occurred in the presence of all three divalent metalloenediynes ions, but reported only minimal degradation when DNA was exposed to free PyED; thus, they concluded that the extent of the chelation-induced radical generation event is strongly metal-dependent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We sought to determine the mechanism by which hyperthermia potentiates metalloenediyne toxicity. In a recent study, Zaleski and co-workers (19) tested the ability of PyED or PyED-metalloenediyne complexes containing Cu(II), Fe (II), and Zn (II) to damage supercoiled DNA. They found that efficient nicking of the DNA occurred in the presence of all three divalent metalloenediynes ions, but reported only minimal degradation when DNA was exposed to free PyED; thus, they concluded that the extent of the chelation-induced radical generation event is strongly metal-dependent.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies showed that when DNA is exposed to Cu(II), Fe(II), and Zn(II) complexes of PyED in the presence of DNA, considerable DNA degradation occurs within 1 h under hyperthermic conditions, with Cu(II) activation producing >50% degradation of DNA within 5 min. The importance of thermally-activated radical production is evidenced by the lack of compromised DNA observed using the cyclized non-radical-generating control complex PyBD, pyridine-2-ylmethyl-(2-{[(pyridine-2-ylmethylene)-amino]-methyl}-benzyl)-amine or free (unmetallated) PyED (19) Additionally, in situ activation of PyED via chelation of Cu(II) and Zn(II) has been shown to result in radical-induced disaggregation of Aβ fibrils at 37 °C relative to the cyclized control PyBD complex. The extent of radical damage is elevated upon treatment under hyperthermic conditions, consistent with the increased radical generation after exposure to elevated temperatures (20).…”
Section: Discussionmentioning
confidence: 99%
“…All syntheses of compounds and subsequent complexations were performed under nitrogen atmosphere employing standard Schlenk and dry box techniques using chemicals of the highest purity available and purchased from commercial sources. The ligand (Z)-N,N′-bis[1pyridin-2-yl-meth-(E)-ylidene]oct-4-ene-2,6-diyne-1,8-diamine (PyED) and metal complexes were prepared using a previously published synthesis (8). Briefly, a cooled methanol solution of PyED (1 eq) was added to a stirring solution of MSO 4 •×H 2 O or MCl 2 •×H 2 O (M=Cu(II), Fe(II), Zn(II); 1 eq) in methanol and stirred for 4 h at 0°C.…”
Section: Synthesis Of Ligands and Metal Complexesmentioning
confidence: 99%
“…In an effort to further evaluate the geometric structure/Bergman cyclization relationship under physiological conditions, we recently reported the preparation of novel PyED-metalloenediyne complexes containing Cu(II), Fe(II), and Zn(II). Bergman cyclization from thermal activation of each of these constructs resulted in diradical generation within 3 h at 37°C (8). A significant metal dependence on the rate of the reaction is observed with these complexes [Cu(II) > Fe(II) > Zn(II)], and reaction rate was directly correlated to efficiency of DNA degradation.…”
Section: Introductionmentioning
confidence: 99%
“…After the chelation with Cu II , Zn II or Mg II , the onset temperatures significantly decreased to 55 °C (Figure B), 125 °C (Figure S4 A), and 100 °C (Figure S4 B), respectively. The greatly accelerated cycloaromatization and the reduction of onset temperature are consistent with the reduction of CD distance after metal coordination with enediyne compounds . Meanwhile, the charge separation assistance in the metal‐ion‐catalyzed Bergman cyclization should not be excluded as well .…”
Section: Resultsmentioning
confidence: 64%